Ray tracing and beyond : phase space methods in plasma wave theory - Tracy, E. R. (Eugene Raymond), 1956-; Brizard, Alain Jean (Cambridge : Cambridge University Press, 2014)
This complete introduction to the use of modern ray tracing techniques in plasma physics describes the powerful mathematical methods generally applicable to vector wave equations in non-uniform media, and clearly demonstrates the application of these methods to simplify and solve important problems in plasma wave theory. Key analytical concepts are carefully introduced as needed, encouraging the development of a visual intuition for the underlying methodology, with more advanced mathematical concepts succinctly explained in the appendices, and supporting Matlab and Raycon code available online. Covering variational principles, covariant formulations, caustics, tunnelling, mode conversion, weak dissipation, wave emission from coherent sources, incoherent wave fields, and collective wave absorption and emission, all within an accessible framework using standard plasma physics notation, this is an invaluable resource for graduate students and researchers in plasma physics.
Introduction -- Some preliminaries -- Eikonal approximation -- Visualization and wave field construction -- Phase space theory of caustics -- Mode conversion and tunneling -- Gyroresonant wave conversion -- Appendix A: Cold plasma models for the plasma dielectric tensor -- Appendix B: Review of variational principles -- Appendix C: Potpourri of other useful mathematical ideas -- Appendix D: Heisenberg-Weyl group and the theory of operator symbols -- Appendix E: Canonical transformations and metaplectic transforms -- Appendix F: Normal forms -- Appendix G: General solutions for multidimensional conversion -- Glossary of mathematical symbols.
Title from publisher's bibliographic system (viewed on 05 Oct 2015).
Keywords: Plasma waves; Ray tracing algorithms; Phase space (Statistical physics)